Analysis of Urban Heat Islands Using Nighttime Land Surface Temperature Data - Chaichana Kulworatit; Jirayu Petchhan (My University, 2025)
This study analyzes Urban Heat Island (UHI) in Thailand using Nighttime Land Surface Temperature (LST) data from the MODIS MYD11A2 dataset, covering 2002-2025, during the winter months (December-January). The research aims to assess heat accumulation in urban areas and identify factors such as heat-absorbing materials, energy consumption, and the lack of green spaces. It also addresses the misconception that water bodies reduce heat, showing that they can contribute to UHI when not managed properly. The data was processed using Google Earth Engine and QGIS to identify UHI zones and calculate Zonal Statistics at the provincial level.
Keywords: Remote Sensing and Land Use; Urban Heat Island Mitigation